1997
DOI: 10.1136/adc.77.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Extensively and partially hydrolysed infant formulas for allergy prophylaxis

Abstract: The allergy preventive eVect of extensively (N) and partially (PH) hydrolysed cows' milk formulas compared with a regular formula (RM) was assessed in 155 infants with a family history of allergy. No cows' milk was given during the first nine months of life and no egg and fish up to 12 months of age. Breast feeding mothers avoided the same foods. At weaning the infants were randomised to one of the formula groups. The cumulative incidence of atopic symptoms at 18 months was 51, 64, and 84% in the N, PH, and RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(126 citation statements)
references
References 29 publications
(15 reference statements)
3
117
2
4
Order By: Relevance
“…As 80–90% of respiratory allergic diseases in children and young adolescents are associated with sensitization to aeroallergens (mainly pollen and house dust mites), it is reasonable to hypothesize that IgE might be involved. However, we did not observe any association between specific IgE measured in serum and hydrolyzates at 15 years, which is consistent with our findings at six and ten years 21, 27 and with reports from the literature 17, 18, 19. Therefore, IgE does not appear to be involved in the observed findings in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As 80–90% of respiratory allergic diseases in children and young adolescents are associated with sensitization to aeroallergens (mainly pollen and house dust mites), it is reasonable to hypothesize that IgE might be involved. However, we did not observe any association between specific IgE measured in serum and hydrolyzates at 15 years, which is consistent with our findings at six and ten years 21, 27 and with reports from the literature 17, 18, 19. Therefore, IgE does not appear to be involved in the observed findings in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Most 11, 12, 13, 14, 15, 16, 17, 18, 19 but not all 7 randomized, controlled trials that have compared different partially and/or extensively hydrolyzed formulas with standard cow′s milk formula (CMF) have confirmed some degree of preventative effect on allergies in the first 2–3 years of life. Results appear especially consistent for eczema 20 within the first year of life.…”
mentioning
confidence: 99%
“…Sample size: a reduction in cumulative incidence of eczema from 30% to 20% at 12 months was considered clinically relevant 17, 18, 19. Assuming 15% dropout, this study required 350 infants randomized before 4 weeks in each arm, to have 80% power to detect this reduction in eczema, using two‐tailed chi‐squared test at a significance of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…However, using the criteria of a 2006 Cochrane review, 41 only 14 randomized or quasirandomized (eg, using alternation) trials in term infants compared the use of partially or extensively hydrolyzed formula with the use of human milk or an adapted cow milk formula. [42][43][44][45][46][47][48][49][50][51][52][53][54][55] All of these trials have followed up with at least 80% of study participants. It is important to note that none of these studies reported any adverse effects, including any adverse effect on infant growth.…”
Section: Role Of Hydrolyzed Formula On the Development Of Atopic Diseasementioning
confidence: 99%
“…49,51,52 Two of these studies found no significant effect, 51,52 and a third study found an OR of 0.45 (95% CI: 0.22-0.94) for partially hydrolyzed formula versus cow milk formula. 49 Three more studies [53][54][55] examined prolonged feeding of extensively hydrolyzed formula compared with partially hydrolyzed formula in 411 infants at high risk of developing allergy. None of these studies found a significant difference in the incidence of atopic dermatitis between the 2 feeding groups.…”
Section: Role Of Hydrolyzed Formula On the Development Of Atopic Diseasementioning
confidence: 99%